-436=6+7(1+8r)

Simple and best practice solution for -436=6+7(1+8r) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -436=6+7(1+8r) equation:



-436=6+7(1+8r)
We move all terms to the left:
-436-(6+7(1+8r))=0
We add all the numbers together, and all the variables
-(6+7(8r+1))-436=0
We calculate terms in parentheses: -(6+7(8r+1)), so:
6+7(8r+1)
determiningTheFunctionDomain 7(8r+1)+6
We multiply parentheses
56r+7+6
We add all the numbers together, and all the variables
56r+13
Back to the equation:
-(56r+13)
We get rid of parentheses
-56r-13-436=0
We add all the numbers together, and all the variables
-56r-449=0
We move all terms containing r to the left, all other terms to the right
-56r=449
r=449/-56
r=-8+1/56

See similar equations:

| .2+x=10* | | x=+9-4x-1 | | 8x-8=9x-16 | | -3(x+5)=7.5 | | -6x=18(7)-6 | | –17+d=3+d−20 | | 2x+1+90+39=180 | | 6(4n+5)=2n-16-n | | -3.8x-5.9x=87 | | 4m+5.2=6m+2.8 | | 4x–8=28 | | 106=8+2(1-8p) | | 2x+56x=-2 | | 7=(2x-1)/3 | | 18=9+9r | | 7(v+4)=84 | | 34=(2x+6) | | 5(a-1)-3(2a+1)=0 | | 3=x+7* | | 4(−8x+5)=−32x–26 | | n=3⋅2(n−1) | | 1+2s=–17s+19s+9 | | 2x+18=x-15 | | 2x=+56x-2 | | 3u+44+u+32=180 | | y=-1*1+3 | | 3r+5=3r-12 | | –7+8t=19t−7−11t | | -4x=-37 | | y=-1*0+3 | | -140=-7(p+6)-7p | | 2|x-9|=14 |

Equations solver categories